Poly(amide-imide)-silica gel hybrids: synthesis and characterization - Avadhani, C. V.; Chujo, Y. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2009)
{Several poly(amide-imide)-silica gel hybrids containing metal salts were prepared by the sol-gel reaction. Poly(amide-imide)s were prepared by low temperature polycondensation reaction of trimellitic anhydride (TMA) and diisocyanates [
Keywords: 2; 4-diphenyl thiophene; 5-Bis(4-carboxymethylene phenyl) 3; poly(amide-hydrazide)s; Thermal properties; Yamazaki's phosphorylation polycondensation